Pengaruh Alkalisasi Terhadap Kekuatan Impak Komposit Epoxy Berpenguat Serat Sisal - Sukadana, I Made; Lokantara, I Putu Lokantara; Agus Suryawan, I Gede Putu; Dwidiani, Ni Made (Teknik Desain Mekanika; Vol 12 No 4 (2023): Oktober 2023 : Teknik Desain Mekanika, 2023)
Abstractt This study aims to determine the effect of alkali treatment on impact strength of sisal fiber reinforced epoxy composites printed using the Hand Lay-Up method with random fiber orientation. The matrix used was 52-id epoxy sikadur using a 30% fiber volume fraction. After testing, the impact strength increased by 32.06% in treated sisal fiber reinforced epoxy composites compared to untreated sisal fiber composites. The impact strength of the specimens treated with alkali was 0.0233 J/mm2, while the epoxy composite with untreated sisal fiber had an impact strength of 0.0176/mm2. Based on these results, it can be concluded that the alkali treatment had an effect on increasing the impact strength of the sisal fiber composites due to the formation of better bonds due to a reduction in the lignin layer on the fibers so that the density of sisal fiber increased by 42.32% after being treated and resulted in a better fiber structure. compact compared to fibers without alkali treatment.. Keywords: Composite, Natural Fiber, Sisal Fiber, NaOH, Hand Lay-Up, Impact Strength